Large Follicular Cyst in a Holstein Cow - Sinem Özlem Enginler*, Mehmet Can Gündüz, Serhat Alkan1 and Feraye Esen2 (Pakistan Veterinary Journal, 2012)
This case report is based on a large follicular cyst (55x42 mm) in a five years old Holstein cow diagnosed by ultrasonography. The serum progesterone (P4) and estradiol 17-β (E2) levels were 2.589 ng/ml and 116.497 pg/ml, respectively at the 1st examination. The cyst started luteinization with the treatment of 10 µg i.m. GnRH and 1000 IU i.v. hCG. On ultrasonographic examination on 9th day, cyst measured 33x31 mm. Following 500 µg PGF2α i.m. administration, the cow exhibited signs of oestrous. Serum collected at this stage revealed P4 and E2 to be 14.438 ng/ml and 141.337 pg/ml, respectively. Three days after the PGF2α application, the ultrasonography revealed the lysis of the luteinized cyst and P4, E2 levels were detected 0.435 ng/ml and 131.067 pg/ml, respectively. Afterward the cow had normal outward appearance. The uterus and ovaries were normal on rectal palpation. The cow was artificially inseminated and became pregnant.